UMP climbs to 103 in the world in 2022 GWUR UI rating - Mimi Rabita, Abdul Wahit (2023)
PEKAN, 12 December 2022 – Universiti Malaysia Pahang (UMP) is ranked 103 compared to 128 in 2021 in the 2022 UI Greenmetric World University Rankings (GWUR) rating.